Ports sustainability - Vujičić, Andrija (Strojniški vestnik, 2013)
The goal of this paper is to present and evaluate the latest trends in the cargo handling equipment (CHE) industry, aimed at mitigating the environmental impact of container terminal operations and contributing to the sustainability of ports. The most common machines for handling containers are described and dealt with separately, with a focus on electric CHE, usually referred to as zero emission CHE. In a separate chapter, recommendations on methodologies suitable for investigation of the environmental footprint of CHE without on-site measuring are reviewed. The life cycle assessment (LCA) methodology as a tool for comparison of conventional and zero emission technology is emphasised with examples. The conventional diesel rubber-tired gantry (RTG) crane and utility tractor rig (UTR) are compared with an electric RTG and UTR using an LCA approach.
Keywords: cargo handling equipment; kontejnerski terminali; life cycle assessment; ničelne emisije; ocena življenjskega cikla; oprema za prekladanje tovora; port container terminals; portalni žerjavi; rubber-tired gantry; tovornjaki za prestavljanje kontejnerjev; utility tractor rig; zero emission